Critiquing the Conception of "Crimes Against Nature": The Necessity for a New "Natural" Law - Gacek, James (International journal of offender therapy and comparative criminology, 2022)
Drawing upon historical developments and legal interpretations of ?crimes against nature? as it relates to bestiality, this paper endeavors to promote further discussions surrounding the conception of ?natural? and/or extant law, by which an understanding of historical and modern objections to crimes against nature opens them up to the critique of thin-universalism?that is, that despite disparate socio-moral fundaments, laws of prohibition coalesce around evangelical totalities. We contend that a paradigm shift in respect of naturalness is necessitated?naturalness should be packaged and represented, in part, by the empirical. Thus, conceptions of vulnerability and sentience rooted in social scientific understandings and in hospitable forms of rights protections ought to provide a new understanding of governance of the natural. In turn, this naturalness ought to be reflected in law so long as the boundaries we propose are not unduly transgressed. If unnatural acts like bestiality have their prohibitions in the legal tethering points of Judeo-Christian and, later Victorian roots, the new natural law ought to be apprised of rights-based constitutionalism and informed by green criminological and animal rights logics. Law, apprised of these ethics, would evolve to expand protections for animals, human and non-human alike. Laws based on the new naturalness could protect species and environments as evidence demands.